1998
DOI: 10.1111/j.1469-7998.1998.tb00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation of wing morphology in three Eurasian populations of the fruit fly, Drosophila lummei

Abstract: Differences in wing morphology are described for three Eurasian populations of Drosophila lummei. A truss network of wing characters was used to quantify wing size and shape for 149 individuals from Japan, Sweden and Russia. Sexual dimorphism in wing size and shape was not substantial, so the sexes were pooled and multivariate analyses conducted. Both principal components analysis and discriminant analysis of wing morphology revealed signi®cant differences among all geographic groups. These differences indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 35 publications
3
18
1
1
Order By: Relevance
“…We found weak evidence for allometry in the wing ratio VR CU , which appeared to decrease with size, but a larger sample size is needed to decide whether or not an outlier does represent the normal range of variation. Morphometric analysis of wing venation in Drosophila lummei Hackman, 1972 did find variation in wing shape consistent with genetic differences in geographically distant populations (Haas & Tolley 1998). However, our ordination of wing dimensions failed to show any variation that was not simply due to size, and suggests that wing ratios may not be informative in the sylvestris-group.…”
Section: Discussioncontrasting
confidence: 44%
“…We found weak evidence for allometry in the wing ratio VR CU , which appeared to decrease with size, but a larger sample size is needed to decide whether or not an outlier does represent the normal range of variation. Morphometric analysis of wing venation in Drosophila lummei Hackman, 1972 did find variation in wing shape consistent with genetic differences in geographically distant populations (Haas & Tolley 1998). However, our ordination of wing dimensions failed to show any variation that was not simply due to size, and suggests that wing ratios may not be informative in the sylvestris-group.…”
Section: Discussioncontrasting
confidence: 44%
“…Shape, however, is more complex. Although many studies have documented shape change in a variety of Drosophila species (Alonso & Munoz, 1984; Cavicchi et al ., 1991; Bitner‐Mathé et al., 1995; Imasheva et al ., 1995; Bublii et al ., 1996; Pezzoli et al ., 1997; Baylac & Penin, 1998; Haas & Tolley, 1998; Huey et al . 2000), there is little evidence indicating that natural shape change is adaptive.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila, wing morphology has been used extensively in taxonomic studies and has revealed marked interspecific divergence (Shorrocks, 1972), with intraspecific variation in the wing size and shape also being frequently demonstrated (Hass and Tolley, 1998;Gilchrist et al, 2000;Hoffmann and Shirriffs, 2002).…”
Section: Introductionmentioning
confidence: 99%